Analisis Kandungan Unsur Hara Makro (N, P, K, Ca, Mg, S), C-Organik dan Kadar Air Pada Lahan Jagung (Zea mays L.) di Desa Biyonga Kecamatan Limboto Kabupaten Gorontalo - Novaldy Damopolii; Fitriyah Suryani Jamin; Nikmah Musa (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
Corn production in Gorontalo Province plays a significant role in supporting both local food needs and export demands. However, corn productivity is highly dependent on soil fertility, particularly the availability of macronutrients. This study aims to: (1) assess the content of macronutrients (N, P, K, Ca, Mg, S), organic carbon (C-organic), and soil moisture in corn fields in Biyonga Village, Limboto Subdistrict, Gorontalo Regency; and (2) discover the differences in the content of these elements between crop rotation systems (Dusun or Hamlet 1) and monoculture systems (Hamlet 3). The study employed a survey method and laboratory analysis of soil samples collected diagonally from two study sites. The finding indicates that the majority of macronutrients, organic carbon, and soil moisture content fall within the low to moderate category. Nutrient levels were found to be higher in the crop rotation system compared to the monoculture system. This suggests that planting patterns significantly influence the availability of nutrients in the soil.